Reconstruction of the family house's memory and sources of interest in over-personal tasks - Zofia Remiszewska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
In the article I used fragments of my research studies, prepared on the basis of narrative interviews. I formulated the main research problem in the form of a question: What is the significance of the family in shaping prosocial attitudes among those who perform over-personal tasks? I am also looking for answers to the following questions: Can you find sources of interest in social issues within your and your family biography? Thanks to the use of narrative interviews, I was able to read and understand elements of the subjects reality. I was able to look into the sources and experiences related to the over-personal tasks of the examined persons. Their subjective interpretations of their behaviors, experiences related to different situations, people and events gave a clear picture about the importance of the family in forming a prosocial profile.